The impact of COVID-19 upon student radiographers and clinical training in Latin America - Solís Barquero, Sergio Manuel (2022)
Introduction: This study aimed to identify the impact of the COVID-19 pandemic upon radiography education across Latin American countries. Methods: A survey containing 20 questions was circulated to radiography students, across 13 universities in 11 countries of Latin America using Google Forms. The survey contained open and closed questions. Answers were analysed with descriptive statistics and the methodology of interpretative phenomenological analysis for the open answers. Results: Of the 1310 responses only 23.9% (n = 313) of students reported attending clinical placements and from this cohort only 8.9% (n = 28) became infected with COVID-19. In response to how the pandemic had impacted upon the students’ academic progression, the most common topic in the open answers was “Concerns about the lack of clinical training”, mentioned by 629 students. Students in middle and later years of their radiography education expressed the greatest concern about future clinical placements. Almost all radiography students (95.2%/n = 1247) indicated that their main concerns regarding COVID-19 infection while undertaking clinical placements was in relation to the risk of infecting their families as most students stated they cohabited with relatives (86.6%/n = 1134). Conclusion: Compared to European findings co-habitation trends increased anxiety related to infection and impacted their mental health. Students expressed concern about the quality of education they were receiving during the pandemic and access to resources to facilitate on-line learning was inadequate. Socio-economic and internet connectivity factors specific to Latin America were identified and these issues need to be addressed if on-line education is required in the future. Implications for practice: The COVID-19 pandemic has impacted Latin America and this study identifies the implications for radiography students related to their clinical and academic training and highlights factors which require consideration to support radiography students as the pandemic continues.